The cost of a divided America: an experimental study into destructive behavior - Wladislaw Mill; John Morgan (Experimental Economics, 2021)
Does political polarization lead to dysfunctional behavior? To study this question, we investigate the attitudes of supporters of Donald Trump and of Hillary Clinton towards each other and how these attitudes affect spiteful behavior. We find that both Trump and Clinton supporters display less positive attitudes towards the opposing supporters compared to coinciding supporters. More importantly, we show that significantly more wealth is destroyed if the opponent is an opposing voter. This effect is mainly driven by Clinton voters. This provides the first experimental evidence that political polarization leads to destructive behavior.
Keywords: C91; D01; D62; D72; D74; 330; Spite; Polarization; Experiment; Hillary Clinton; Donald trump